MITOLOGÍA Y ESTILÍSTICA CARTARESQUIANAS EN SOLENOIDE Y EMINESCU: EL SUEÑO QUIMÉRICO (EMINESCU: VISUL CHIMERIC). LAS PERSPECTIVAS DEL AUTOR Y DE ALGUNOS CRÍTICOS / CARTARESQUIAN MYTHOLOGY AND STYLISTICS IN SOLENOID AND EMINESCU: THE CHIMERICAL DREAM (EMINESCU: VISUL CHIMERIC). THE PERSPECTIVES OF THE AUTHOR AND SOME CRITICS - Felix Nicolau (Incursiuni în imaginar)
The article will focus on two books by Mircea Cărtărescu, Eminescu: The Chimerical Dream (Eminescu: Visul chimeric, Humanitas, 2011), originally his bachelor’s thesis, and Solenoid, the massive novel of 2015. The intention is to see how the archetypes, complexes, themes and motifs of fiction (and autofiction) influence the author’s theoretical approaches. The interpretations of literary critics and historians Alex Ștefănescu and N. Manolescu will also be analyzed to establish a starting point for the critical analysis. Therefore, the research will attempt a Cărtăresquian mythocriticism in combination with a study of critical reception. Additionally, it is of great importance to notice how the aesthetic categories of grotesque, sublime, and pathos inform narratives built with maximalist stylistic means. The focus of the research is to identify the degree of innovation and originality in a quantitatively imposing literary prose. In this respect, studying Cărtărescu masterful mingling of phantasy and sentimentalized realism proved to be of great help in understanding the peculiar narrative and hermeneutic strategies used bu the autor.